The Positive Impact of Physical Activity on the Mental Health of Children with Special Needs: Literature Study - Ica, Lade; Suwo, Rahedin; Sabrin, Laode Maklum; Haris, Iyan Nurdiyan; Rosti, Rosti (Jurnal Pendidikan Jasmani (JPJ), 2025)
This research aims to explore the positive impact of physical activity on the mental health of children with special needs (ABK) through a literature study. A review was conducted of 15 main studies that discussed the effects of physical activity on children with special needs, such as children with autism, ADHD, cerebral palsy and other developmental disorders. The results of the analysis show that physical activity can significantly reduce symptoms of stress, anxiety and depression, as well as improve children's mood, social skills and quality of life. Group activities, such as team sports, have been shown to be most effective in improving communication skills and social interaction. The ideal duration of physical activity to provide a positive mental impact is 30-60 minutes per session, with a minimum frequency of three times a week. This research also highlights the importance of implementing structured physical activity programs in inclusive schools and therapy centers, as well as the need for further research in Indonesia to adapt global findings to local contexts. The conclusion of this study is that physical activity can be an effective non-pharmacological intervention to improve the mental health of ABK, with the support of parents, teachers and researchers in developing appropriate programs.